Distribution and relevance of aufeis (icing) in the Upper Indus Basin - Brombierstäudl, Dagmar; Schmidt, Susanne; Nüsser, Marcus (The science of the total environment, 2021)
In the semi-arid high mountains of the Upper Indus Basin (UIB), meltwater supply from the cryosphere is vital for irrigated agriculture and hydropower generation. An overlooked cryosphere component that is critical for this is aufeis, which appears as a sheet-like formation of ice layers, created by successive and laminated freezing of flowing water. This study aims to redress the lack of knowledge about this phenomenon by creating an inventory of aufeis fields for the UIB and analysing their spatial distribution, including the role of topographical parameters such as altitude, slope, and aspect. The study is based on a time-series analysis using Landsat imagery from 2010 to 2020, supported and validated by several field campaigns carried out between 2014 and 2020. In total, more than 3700 aufeis fields were detected covering an area of about 298 ± 38 km2. The spatial distribution of their occurrence indicates a distinct elevation range between 4000 and 5500 m a.s.l. and is marked by a pronounced longitudinal increase to the east. In contrast to the western part of the UIB (Gilgit-Baltistan), where only some few and small aufeis fields can be detected, 65% of the aufeis covered areas (195 ± 23 km2) exist on the Tibetan Plateau. Our database fills an important research gap and will help in further cryosphere studies in the UIB and beyond.
Gesehen am 30.04.2021